Determinants of access to primary healthcare for formerly incarcerated women transitioning into the community: a systematic review of the literature - Volker Winkler; Babak Moazen; Marie Claire Van Hout; Heino Stover; Nisreen Agbaria; Margit Wirth (BMJ Publishing Group, 2024)
Background Women with a history of incarceration experience significantly poorer health outcomes and encounter barriers to accessing healthcare, both during incarceration and after release. These challenges are more pronounced compared with both their male counterparts and women in the general population. We conducted a systematic literature review to respond to the following research questions: (1) what are the determinants of primary healthcare uptake and retention among formerly incarcerated women transitioning into the community? and (2) what are the barriers and facilitators for their access to primary healthcare postrelease?Methods Following the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and drawing on Levesques' Patient-Centered Access to Healthcare Model, we searched and identified relevant publications from 2012 onwards in the following databases: PubMed, CINAHL, PsychInfo, Web of Science databases and Google Scholar. Records were included if they reported primary healthcare among formerly incarcerated women. Findings from the included studies were extracted and arranged under relevant themes using convergent-integrated approach.Findings A total of 3524 records were identified and reviewed, from which 37 publications were included in the review. Five main themes emerged as follows: (1) trends and predisposing factors, (2) barriers and facilitators to care, (3) continuity of care and arrangement between the prison and community health providers, (4) prescriptions and health insurance enrolment and (5) interventions to improve primary healthcare utilisation postrelease. Additional sub-themes, such as perceived discrimination in the healthcare system and delays in cancer screening, were identified and discussed.Conclusion The findings of the systematic review underscore the ongoing challenges women face in accessing primary care when transitioning from incarceration to the community. Enhancing coordination efforts between prison services and community healthcare providers requires a comprehensive assessment of women's healthcare needs during this transition, alongside evaluating the availability of transitional programmes. Further research is required to explore the long-term impact of such programmes and to address the gaps in evidence from low- and middle-income countries.